Thymoquinone Reduces Oxidative and Nitrosative Stress in Tongue-tissue of Rats Exposed to Total Cranial Irradiation - ADLI, MUSTAFA (UNIV WEST INDIES FACULTY MEDICAL SCIENCES, 2016)
Introduction: Head and neck cancer patients treated with radiotherapy suffer severe side-effects during and following their treatment. Efforts to decrease toxicity of irradiation to normal tissue, organs and cells have led to a search for cytoprotective agent. Investigations for effective and non-toxic compounds with radioprotective capability led to increasing interest in antioxidant such as thymoquinone (TQ). Objective: The aim of this study was to evaluate the radioprotective effects of TQ on oxidant/antioxidant systems in the tongue-tissue of rats exposed to total cranial irradiation. Materials and Methods: Thirty-two rats were divided into four groups to test the radioprotective effectiveness of TQ administered by either orogastric tube or intraperitoneal injection. Appropriate control groups were also studied. Results: Tongue glutathione peroxidase (GSH-Px), glutathione-S-transferase (GST), total superoxide scavenger activity (TSSA), non-enzymatic superoxide scavenger activity (NSSA), and superoxide dismutase (SOD) activities in the control and sham control groups were significantly increased when compared to the irradiation (IR) group and IR plus TQ groups. Nitric oxide (NO center dot), peroxynitrite (ONOO) and malondialdehyde (MDA) levels, xantine oxidase (XO) and nitric oxide synthase (NOS) activities significantly increased in the IR group when compared to the control and sham control groups. Conclusion: Results show that TQ has the radioprotective, antioxidant effects and free radical scavenging activity. Therapy with antioxidants may lead to the increase in the antioxidant defense system and thus, may decrease the clinical symptoms in radiation therapy.
Keywords: Antioxidant enzymes; irradiation; oxidative stress; thymoquinone; tongue-tissue